Vaccinations at home: a new strategy to contain vaccine hesitancy? The experience of ASL Napoli 1 Centro, Italy - Tesorone, Marina; Ungaro, Carla; Graziano, Luisa; Vitagliano, Anna; Luminoso, Ida; Corvino, Maria; Papa, Marco; Verdoliva, Ciro (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Vaccination coverage are generally geographically variable, even within large cities; furthermore, across target population are embedded difficult-to-reach clusters. To address this issue and improve coverage of mandatory vaccinations, a study group explored bringing vaccination at home as an interventional strategy. In a pilot experience, parents of unvaccinated and under vaccinated children of the 2020 birth cohort living in Naples, Italy were contacted by telephone to offer home administration of vaccinations. A specifically trained team arranged vaccinations visits at home. Coverage rates were evaluated at baseline and one month after the intervention strategy. A significant positive increase in hexavalent vaccine (+1.43%) and measles-mumps-rubella (+1.85%) coverage was registered despite the short duration of the pilot program. Home vaccination turned out to be a medical resource consuming but feasible and successful strategy to increase mandatory vaccinations coverage among the most difficult-to-reach and fragile segments of the pediatric population.